704The preventable future burden of cancer in Australia. (2nd September 2021) - Laaksonen, Maarit A; Canfell, Karen; MacInnis, Robert; Arriaga, Maria E; Hull, Peter; Banks, Emily; Giles, Graham G; Mitchell, Paul; Cumming, Robert G; Byles, Julie E; Magliano, Dianna J; Shaw, Jonathan; et al.
Abstract: Background: Estimates of the future burden of invasive cancer attributable to current modifiable causal exposures can guide cancer prevention. Methods: We linked pooled data from seven Australian cohort studies (N = 367, 058) to national cancer and death registries, and estimated exposure-cancer and exposure-death associations using adjusted proportional hazards models. We estimated exposure prevalence from contemporary national health surveys and calculated population attributable fractions (PAFs) and 95% confidence intervals, using advanced methods accounting for competing risk of death. Results: Current levels of past and current smoking explain 36.1% (95%CI 33.2%-38.9%), body fatness 13.6% (10.9%-16.2%) and alcohol consumption exceeding two drinks/day 2.3% (1.0%-3.6%) of cancers causally related to these exposures, corresponding to 210, 000, 81, 300 and 14, 800 cancers in Australia in the next 10 years, respectively. Ever smoking is the leading modifiable cause of lung (82.1%), bladder (49.8%), oesophageal (42.8%), liver (39.8%), head and neck (35.6%), and pancreatic (21.3%) cancer burden. Body fatness is the leading modifiable cause of corpus uteri (42.5%), gastric cardia (33.6%), renal cell (29.1%), thyroid (20.1%), colorectal (12.6%) and postmenopausal breast (12.6%) cancer burden. The absolute numbers of cancers in the next 10 years attributable to smoking are highest for lung cancer (114, 000). The numbers of cancers attributable to body fatness and alcohol are highest for colorectal cancer (23, 000 and 9, 900, respectively). Conclusions: More reliable advanced methods demonstrate large proportions and numbers of cancers are preventable by modifying behaviours. Key messages: Ever smoking and body fatness are the leading causes of preventable future burden of causally related cancers in Australia.